2020
DOI: 10.5603/gp.2020.0014
|View full text |Cite
|
Sign up to set email alerts
|

Can coffee consumption be used to accelerate the recovery of bowel function after cesarean section? Randomized prospective trial

Abstract: Objectives: To evaluate whether coffee consumption accelerates the recovery of bowel function after cesarean section or not. Material and methods: This study was designed as randomized controlled study. Patients were randomly assigned to one of two groups: Ultimately, Group 1 (n = 51) was the study group and drank three cups of coffee after cesarean, whereas group 2 (n = 52) was not given any treatment. The primary outcome measure was the time to first defecation after surgery, the secondary outcomes were time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
1
6
0
2
Order By: Relevance
“…Many scholars at home and abroad have conducted in-depth research on the influencing factors of gastrointestinal function recovery. For example, Bozkurt Koseoglu et al found through research that the ERAS concept can not only speed up the recovery of patients after surgery but also improve patients' recovery and quality of life [ 5 ]; Cao et al found that moxibustion is better than Western medicine nursing treatment [ 6 ]; Hu et al found through experiments that acupuncture and moxibustion are helpful for the early recovery of gastrointestinal function after surgery [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many scholars at home and abroad have conducted in-depth research on the influencing factors of gastrointestinal function recovery. For example, Bozkurt Koseoglu et al found through research that the ERAS concept can not only speed up the recovery of patients after surgery but also improve patients' recovery and quality of life [ 5 ]; Cao et al found that moxibustion is better than Western medicine nursing treatment [ 6 ]; Hu et al found through experiments that acupuncture and moxibustion are helpful for the early recovery of gastrointestinal function after surgery [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, 27 studies were included in the qualitative synthesis. The 27 studies comprised 9 ongoing trials (NCT 02510911, NCT02639728, NCT03143621, NCT03191877, NCT03712891, NCT04205058, NCT04547868, IRCT20200116046153N1, and CTRI/2021/04/033141), 5 protocols without results (NCT00130026, NCT01130675, NCT02250924, NCT03660267, and NCT03815877), and 13 clinical trials (1246 patients) [21][22][23][24][25][26][27][28][29][30][31][32][33]. Table 1 shows the characteristics of the included clinical trials.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 shows the characteristics of the included clinical trials. Of the 13 trials [21][22][23][24][25][26][27][28][29][30][31][32][33], 6 were on colorectal surgery, 5 on cesarean section, and 2 on gynecological surgery. The intervention was caffeinated coffee in 10 trials and decaffeinated coffee in 3 trials.…”
Section: Resultsmentioning
confidence: 99%
“…Son 10 yılda ise ameliyat sonrası dönemde hastaların kahve tüketiminin bağırsak fonksiyonları üzerine etkilerinin incelendiği randomize kontrollü klinik araştırmaların arttığı belirlenmiştir. Bu çalışmalar kolorektal cerrahi [24][25][26][27][28] , jinekolojik cerrahi 29,30 geçiren hastalarla ve sezaryan [31][32][33][34] olan kadınlarla yürütülmüştür.…”
Section: Kahve Tüketimiunclassified
“…Literatürde spinal anestezi altında sezaryen doğum yapan kadınlarla yürütülen çalışmalarda kahve tüketiminin bağırsak fonksiyonlarını hızlandırmada olumlu etkilerinin olduğu belirlenmiştir [31][32][33][34] . Bu çalışmalarda hastalara kahve verilme sıklığı günde üç kez olup miktarı 100 ml olarak düzenlenmiştir.…”
Section: Kahve Tüketimiunclassified